Evaluation of hs-CRP and visseral adiposity index in patients with policystic ovary syndrome by clinical and laboratory findings. (September 2016) - Ün, B.; Dolapçıoğlu, K.S.; Güler Okyay, A.; Şahin, H.; Beyazıt, A.
Abstract: Aim: In this study, we aimed to evaluate two cardiovascular risk markers, hs-CRP and visseral adiposity index, in patients with policystic ovary syndrome in association with clinical and laboratory findings. Material and method: Study group included 75 patients who were diagnosed as PCOS according to the criteria of AE-PCOS 2006 and control group included 75 non-PCOS patients who were subsequently admitted to outpatient clinic for smear control, with urinary or vaginal symptoms. Physical and sonographic examinations were made to all subjects. Mean arterial pressure, waist/hip ratio and body mass index were calculated. Fasting blood glucose and insulin, HbA1c, lipids, high sensitivity C-reactive protein (hs-CRP), estradiol, follicle stimulating hormon, luteinising hormone, tiroid stimulating hormone, prolaktin, total testosteron and sex hormone binding globulin were tested in venous blood samples collected from cases following overnight fast in follicular phase of spontaneous or induced menstruation. Visceral adiposity index was also calculated. Findings: No statistically significant difference was found between PCOS group and control group concerning hs-CRP and VAI ( p > 0.05). When patients in PCOS group were further grouped as obese and non-obese, hs-CRP and VAI values in obese group were significantly higher than those in non-obese group ( p < 0.001). However, when control group were further grouped as obese and non-obese, there was no significant difference in terms of hs-CRP between groups ( p > 0.05), VAI values were significantly higher in obese control group ( p < 0.05). Conclusion: According to the results of our study, hs-CRP stands for a better and more specific marker than VAI to determine metabolic components and predictive risks for cardiovascular diseases in patients with PCOS. Further studies with larger populations are needed in order to determine cardiovascular risks particularly in young PCOS patients.